CO2 methanation over low-loaded Ni-M, Ru-M (M = Co, Mn) catalysts supported on CeO2 and SiC - Chopendra G. Wasnik; Maki Nakamura; Taiki Shimada; Hiroshi Machida; Koyo Norinaga (Carbon Resources Conversion)
The concentration of the major greenhouse gas CO2 is rapidly increasing in the atmosphere, leading to global warming and a range of environmental issues. An efficient circulation and utilization of CO2 is critical in the current environmental context. Methanation, an exothermic process, emerges as a critical strategy for effective CO2 utilization. On this front, there is a significant demand for rational design of catalysts that maintain high activity and methane selectivity over a wide temperature range (250–550 °C). The catalyst that can promise a consistent reaction even at 500 °C under an atmospheric pressure is thus obliged. The present study investigated bimetallic catalysts with SiC, which is known for its exceptional thermal conductivity, and CeO2, which is characterized by its CO₂ affinity, as base materials. We incorporated Ni-M and Ru-M (M = Co and Mn) as the active metals, each loaded at 2 %. Impressively, with merely 20 mg, the Ni-Co/SiC catalyst achieved a CO2 conversion rate of 77 % and CH₄ selectivity of 88 % at 500 °C, in a fixed-bed tubular reactor system with conditions of H2/CO2 = 4, a total flow rate of 70 ml min−1, and a steady GHSV of 12,000 h−1. Moreover, 2Ni-2Co/CeO2 catalyst demonstrated exceptional performance with a 76 % conversion of CO2 and a 83 % selectivity for CH4, all under identical conditions. The catalyst's durability was confirmed by a subsequent 40-hour stability test, which showed only a 3–5 % degradation. The developed catalysts were comprehensively characterized by BET/BJH, CO pulse chemisorption, H2-TPR, HAADF-STEM-EDS, SEM-EDS and XRD etc. to unveil their physicochemical and surface traits. It was found that Co and Mn, when integrated, effectively restrained the agglomeration of Ni and Ru particles, ensuring optimal metal dispersion on the support. In conclusion, our synthesized bimetallic catalysts shown a sustained catalytic capability, even in the high-temperature environment.